Las denominaciones de la mujer anciana en la lengua latina: interpretación etnolingüística - Pascual Lopez, Xavier (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
Ethnolinguistic approach allows to track cultural information included in language, especially lexical and phraseological units. From this perspective, the language tells us about the particular way a linguistic-cultural community perceives reality. Society attributes to women a number of features, qualities, defects and social functions. These traits shape a cultural image of women, and this biased picture is functional in social relationships and it is reflected on the terms a language uses to refer to women. The purpose of this paper is to describe the perception of old women in Roman society by means of the associations and connotations carried by Latin terms anus, anicula and vetula.